2009
DOI: 10.1038/sj.bjc.6605243
|View full text |Cite
|
Sign up to set email alerts
|

CA 19-9 as a biomarker in advanced pancreatic cancer patients randomised to gemcitabine plus axitinib or gemcitabine alone

Abstract: BACKGROUND: Response assessment in advanced pancreatic cancer (APC) is difficult and predictive markers are needed. There are insufficient data on the value of carbohydrate antigen 19 -9 (CA 19-9) and cytostatic-targeted therapies. Axitinib, a selective vascular endothelial growth factor (VEGF) receptors 1, 2, 3 inhibitor, may increase overall survival (OS) in APC. METHODS: We assessed serum CA 19-9, clinical outcomes and diastolic blood pressure (dBP) in APC patients receiving gemcitabine plus axitinib (Gem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…In the current study, both CA19-9 and CEA were statistically significant prognostic factors in univariate analysis, but only CEA remained significant after multivariable analysis with a Cox proportional hazard model. Some authors reported a prognostic role of CA19-9 for metastatic pancreatic cancer [21,22], but others reported that CEA was more important than CA19-9 [23,24], like our study. Serum level of LDH has been thought to correlate with tumor burden and reflect rapid tumor growth.…”
Section: Discussionsupporting
confidence: 58%
“…In the current study, both CA19-9 and CEA were statistically significant prognostic factors in univariate analysis, but only CEA remained significant after multivariable analysis with a Cox proportional hazard model. Some authors reported a prognostic role of CA19-9 for metastatic pancreatic cancer [21,22], but others reported that CEA was more important than CA19-9 [23,24], like our study. Serum level of LDH has been thought to correlate with tumor burden and reflect rapid tumor growth.…”
Section: Discussionsupporting
confidence: 58%
“…Numerous studies have evaluated CA19‐9 with respect to its value both as a prognostic and predictive marker. The prognostic value of baseline CA19‐9 has been demonstrated multiple times over, with lower levels of CA19‐9 associated with improved outcomes 9‐14. Similarly, others have suggested that a treatment‐related decline in serum CA19‐9 is predictive of response to treatment.…”
mentioning
confidence: 83%
“…Carbohydrate antigen 19.9 (CA 19.9) is a widely accepted surrogate marker for treatment response, although it has only modest sensitivity and specificity [38]. Furthermore, K-ras wild type status appeared to derive better survival from erlotinib than K-ras mutant tumor, and so did patients who developed rash during erlotinib treatment.…”
Section: Biological Therapy In Pancreatic Cancermentioning
confidence: 99%